ودورها في ضبط الوارداتALGEX دور المنصات الرقمية كآلية للرقابة على التجارة الخارجية في الجزائر منصة طلب رخص الاستيراد من طرف - سلخان، هنية; عمامره، محمد يوسف (University Of Eloued جامعة الوادي, 2024)
تهدف الدراسة إلى استكشاف وتوضيح دور المنصات الرقمية الحكومية، وخاصة منصة متابعة عمليات الاستيراد (ALGEX)، في متابعة عمليات الاستيراد وتعزيز الرقابة على التجارة الخارجية بالجزائر، مع التركيز على تحسين كفاءة عمليات الاستيراد ومراقبة المخزونات من السلع المستوردة وكذا حجم الواردات ومصادرها، بالاضافة الى زيادة الشفافية ومكافحة الفساد. اعتمدت الدراسة على المنهج الوصفي التحليلي لتقييم آلية عمل المنصة وتأثيرها على عمليات التجارية الدولية وكذا الاطراف الفاعلة. وقد أظهرت نتائج الدراسة أن المنصة ساهمت في ضبط المخزونات المحلية، مراقبة استخدام العملة الصعبة، وتقليل التجاوزات في مجال الاستيراد، مما عزز الشفافية والكفاءة. ومع ذلك، يُعد طول فترة معالجة الطلبات تحديًا يثقل كاهل المستوردين بتكاليف إضافية. Abstract: The study aims to explore and clarify the role of government digital platforms, particularly the platform for monitoring import operations (ALGEX), in tracking import activities and enhancing control over foreign trade in Algeria. The focus is on improving the efficiency of import processes, monitoring inventories of imported goods, as well as the volume and sources of imports. Additionally, the study highlights the platform's contribution to increasing transparency and combating corruption. The study adopts a descriptive-analytical approach to evaluate the platform's operational mechanism and its impact on international trade activities and stakeholders. The findings reveal that the platform has contributed to regulating local inventories, monitoring the use of foreign currency, and reducing irregularities in the import sector, thereby enhancing transparency and efficiency. However, the extended processing time for applications poses a challenge, burdening importers with additional costs.
The Role of Digital Platforms as a Mechanism for Monitoring Foreign Trade in Algeria
مداخلة
Keywords: المنصات الرقمية; الشفافية; المخزونات; الإستراد; منصة ALGEX; digital platforms; transparency; inventories; imports; ALGEX platform